Production of Bio-hydrocarbon from Refined-Bleach-Deodorized Palm Oil using Micro Activity Test Reactor - Mansur, Dieni; Aminuddin, Aminuddin; Wargadalam, Verina J (Reaktor, 2020)
Catalytic cracking of vegetable oil for the production of bio-hydrocarbons had been developed. In this study, the catalytic cracking of Refined-Bleach-Deodorized Palm Oil (RBDPO) had carried out over Fluid Catalytic Cracking Unit (FCCU) equilibrium catalyst in a micro activity test reactor at 510Â°C under various catalyst to oil (CTO) ratio of 1.20 - 2.01 g/g. The catalytic cracking of RBDPO had produced the organic liquid product (OLP) containing bio-hydrocarbon, water, gas, and coke on the catalyst converted to CO2 during the catalyst regeneration process. The increase in CTO ratio from 1.20 to 2.01, OLP yield decreased from 80.48% to 70.12%. The OLP was separated into gasoline, light cycle oil (LCO), and heavy cycle oil (HCO) based on boiling point difference by a simulated distillation gas chromatography (SimDis GC). High gasoline fraction as 31.56% was produced at CTO of 2.01 g/g. The gasoline fraction contained olefins, aromatics, paraffin, iso-paraffins, and a small amount of naphthenes and oxygenates. The presence of chemicals in the gasoline fraction influenced the research octane number (RON) of the fuel.Keyword: bio-hydrocarbon; catalytic cracking; micro activity test reactor; RBDPO